Legal Protection for Consumers Who Suffer Losses Due to Purchased Goods Which Are Counterfeit Barcode Products According to Law Number 8 of 1999 Concerning Consumer Protection - Devi Christina Octaviani Tamba; Janpatar Simamora; Meli Hertati Gultom (Journal of Legal and Cultural Analytics, 2025)
Law No. 8 of 1999 on Consumer Protection (UUPK) regulates consumer protection in Indonesia. This study aims to analyze the legal protection provided to consumers who suffer losses from purchasing products with fake barcodes, which can confuse consumers regarding regulations related to E-commerce transactions. Online business operators are required to ensure the authenticity, quality, and safety of products. The primary focus of this research is how consumers who incur losses from purchasing products with fake barcodes are legally protected. According to the Consumer Protection Law (UUPK), consumers are entitled to receive goods that match the information promised by the business operator and are entitled to compensation for any loss incurred. Consumers may suffer both material and immaterial losses, such as damaged goods, financial loss, and health risks. Additionally, business operators involved in barcode forgery may face administrative and criminal sanctions. Therefore, the UUPK provides a firm legal foundation to protect consumers' rights in cases involving products with fake barcodes.